Why do patients with chronic illnesses fail to keep their appointments? A telephone interview - Zailinawati, A.H.; Ng, Chirk Jenn; Nik-Sherina, H. (SAGE Publications, 2006)
Missed appointments affect patients' health in addition to reducing practice efficiency. This study explored the rate and reasons of non-attendance among patients with chronic illnesses. It was a cross-sectional descriptive study carried out in a family practice clinic over a one-month period in 2004. Those who failed to turn up for scheduled appointments were interviewed by telephone based on a structured questionnaire. Out of 671 patients, the non-attendance rate was 16.7. Sixty-seven percent of non-attenders were successfully interviewed. Males (p=0.01), Indians (p=0.015), patients with coronary artery disease (p=0.017), multiple diseases ( >= 4) (p=0.036) and shorter appointment intervals (p=0.001) were more likely to default. The main reasons for non-attendance were: forgot the appointment dates (32.9), not feeling well (12.3), administrative errors (19.1) and work or family commitments (8.2). The majority would prefer a reminder through telephone (71.4), followed by letters (41.3). In conclusion, appropriate intervention could be taken based on the reasons identified in this study.